Leukocyte phosphodiesterase expression after lipopolysaccharide and during sepsis and its relationship with HLA‐DR expression. Issue 6 (29th March 2017) - Lelubre, Christophe; Medfai, Hayfa; Akl, Israa; Leentjens, Jenneke; Kox, Matthijs; Pickkers, Peter; Rousseau, Alexandre; Biston, Patrick; Piagnerelli, Michael; Vanhaeverbeek, Michel; Uzureau, Pierrick; Vincent, Jean‐Louis; et al.
Abstract : Endotoxemia and sepsis are associated with different PDE mRNA expression patterns, which may be related to some aspects of septic immune dysregulation. Abstract : Phosphodiesterases (PDEs) may modulate inflammatory pathways, but PDE expression is poorly documented in humans with sepsis. Using quantitative PCR on whole blood leukocytes, we characterized PDE mRNA expression in healthy volunteers ( n = 20), healthy volunteers given lipopolysaccharide (LPS; n = 18), and critically ill patients with ( n = 20) and without ( n = 20) sepsis. PDE4B protein expression was also studied in magnetic‐activated cell sorting (MACS)–isolated CD15 + neutrophils (from 7 healthy volunteers, 5 patients without and 5 with sepsis). We studied relationships between PDE expression, HLA‐DR (mRNA and expression on CD14 + monocytes), tumor necrosis factor (TNF)‐α, and interleukin (IL)‐10 levels. LPS administration in volunteers was associated with increases in PDE4B and PDE4D and decreases in PDE4A and PDE7A mRNAs. The observed global down‐regulation of the HLA‐DR complex was correlated with PDE7A. Critically ill patients had lower TNF‐α/IL‐10 mRNA ratios than the volunteers had and global down‐regulation of the HLA‐DR complex. Septic patients had persistently lower mRNA levels of PDE7A, PDE4A, and 4B (also at a protein level) and decreasing levels of PDE4D over time. Low PDE4D mRNA levels correlated negatively with HLA‐DMA and HLA‐DMB. LPS administration and sepsis are, therefore, associated with different PDE mRNA expression patterns. The effect of PDE changes on immune dysfunction and HLA‐DR expression requires further investigation.